2023
DOI: 10.3847/1538-4357/accb86
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Drivers and Observational Tracers of CO-to-H2 Conversion Factor Variations in Nearby Barred Galaxy Centers

Abstract: The CO-to-H2 conversion factor (α CO) is central to measuring the amount and properties of molecular gas. It is known to vary with environmental conditions, and previous studies have revealed lower α CO in the centers of some barred galaxies on kiloparsec scales. To unveil the physical drivers of such variations, we obtained Atacama Large Millimeter/submillimeter Array bands (3), (6), and (7) observations toward the inner ∼2 kpc of NGC 3627 and NGC 4321 tracing 12CO, 13CO, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 125 publications
1
10
0
Order By: Relevance
“…Lower values of X CO have been observed in the bars and bar lanes of other spiral galaxies (e.g., Meier & Turner 2001;Bolatto et al 2013;Teng et al 2022Teng et al , 2023Sormani et al 2023). Our results are consistent with and offer additional explanations for these results.…”
Section: Accretion Rate Onto the Cmzsupporting
confidence: 89%
“…Lower values of X CO have been observed in the bars and bar lanes of other spiral galaxies (e.g., Meier & Turner 2001;Bolatto et al 2013;Teng et al 2022Teng et al , 2023Sormani et al 2023). Our results are consistent with and offer additional explanations for these results.…”
Section: Accretion Rate Onto the Cmzsupporting
confidence: 89%
“…In those environments, α CO can be 5-15 times lower than the Galactic disk value (Ackermann et al 2012;Sandstrom et al 2013;Israel 2020;Teng et al 2022Teng et al , 2023den Brok et al 2023). The lower α CO in galaxy centers is likely driven by CO emissivity variations due to higher excitation and/or stronger dynamical effects, such as turbulence or inflowing gas (Narayanan et al 2012;Papadopoulos et al 2012;B13;Gong et al 2020;Teng et al 2023). These effects may also explain the low α CO seen in mergers or (ultra)luminous infrared galaxies (U/LIRGs; Downes & Solomon 1998;Krieger et al 2017;Sliwa et al 2017;Cicone et al 2018;Herrero-Illana et al 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Thanks to the high resolution and sensitivity of the Atacama Large Millimeter/submillimeter Array (ALMA), CO (isotopologue) observations are now routinely possible at cloud scales in nearby galaxies (e.g., Leroy et al 2021;Davis et al 2022;Koda et al 2023;Williams et al 2023). In particular, recent studies modeling multi-CO isotopologues in nearby galaxy centers have revealed that CO opacity is the dominant driver of α CO variations (Israel 2020;Teng et al 2022Teng et al , 2023. This strong dependence of α CO on CO opacity further leads to a clear anticorrelation between α CO and the observed line width at ∼100 pc scales in barred galaxy centers (Teng et al 2023, hereafter T23).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations